Proximal tibial trabecular bone mineral density is related to pain in patients with osteoarthritis - Wadena D. Burnett; Saija A. Kontulainen; Christine E. McLennan; Diane Hazel; Carl Talmo; David R. Wilson; David J. Hunter; James D. Johnston (Arthritis Research & Therapy, 2017)
Abstract Background Our objective was to examine the relationships between proximal tibial trabecular (epiphyseal and metaphyseal) bone mineral density (BMD) and osteoarthritis (OA)-related pain in patients with severe knee OA. Methods The knee was scanned preoperatively using quantitative computed tomography (QCT) in 42 patients undergoing knee arthroplasty. OA severity was classified using radiographic Kellgren-Lawrence scoring and pain was measured using the pain subsection of the Western Ontario and McMaster Universities Arthritis Index (WOMAC). We used three-dimensional image processing techniques to assess tibial epiphyseal trabecular BMD between the epiphyseal line and 7.5 mm from the subchondral surface and tibial metaphyseal trabecular BMD 10 mm distal from the epiphyseal line. Regional analysis included the total epiphyseal and metaphyseal region, and the medial and lateral epiphyseal compartments. The association between total WOMAC pain scores and BMD measurements was assessed using hierarchical multiple regression with age, sex, and body mass index (BMI) as covariates. Statistical significance was set at p < 0.05. Results Total WOMAC pain was associated with total epiphyseal BMD adjusted for age, sex, and BMI (p = 0.013) and total metaphyseal BMD (p = 0.017). Regionally, total WOMAC pain was associated with medial epiphyseal BMD adjusted for age, sex, and BMI (p = 0.006). Conclusion These findings suggest that low proximal tibial trabecular BMD may have a role in OA-related pain pathogenesis.